Induktive Lehrverfahren im Fremdsprachenunterricht. Der Versuch einer zeitgemäßen Bestimmung des Begriffs und seiner Funktion in historischer Perspektive - HOSTYŃSKI, Paweł (Wydawnictwo Naukowe UAM, 1996)
The following article attempts to analyse the concept of induction and its function in the mainstream methods in foreign language teaching. The paper presents the results of the research carried out on the effectiveness of the application of inductive vs. deductive approach. It also describes the influence of the collected experiences on the modern glottodidactic view according to the inductive or deductive approach. Throughout the description of past and present trends, the author demonstrates the understanding of induction, starting from its source meaning, through its meaning in glottodidactics, to terms related to various ways of inductive teaching.